Composite sodium supplementing material and preparation method thereof, positive pole piece, battery and electric device
By using composite sodium supplement materials, including carbon-coated sodium supplement materials, the problem of active sodium consumption during the first charge of the sodium battery is solved, and the effect of high capacity utilization and long cycle life is achieved.
Patent Information
- Application Number
- CN202311129570.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-09-04
AI Technical Summary
Existing lithium batteries face the problem of shortage of lithium resources, and the solid electrolyte boundary membrane formed by the sodium batteries during the first charge will irreversibly consume the active sodium of the positive electrode, resulting in low first discharge capacity and Coulomb efficiency.
A composite sodium supplement material is used, which includes a matrix and a carbon cladding layer located on the surface of the substrate part, the matrix includes a sodium supplement material, and the carbon cladding layer includes an inorganic carbon material and an organic carbonized material. By adjusting the proportion of sodium supplementary materials, inorganic carbon materials and organic carbon sources, the electronic conductivity and capacity utilization of the material are improved.
It achieves low oxidation potential, high theoretical capacity and high capacity utilization, improves the first discharge capacity and Coulomb efficiency of the battery, and extends the cycle life of the battery.
Smart Images

Figure CN119560514A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a composite sodium supplement material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] In recent years, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. At present, lithium batteries still occupy the core position of batteries, and lithium batteries are also facing great challenges, such as the increasing shortage of lithium resources. Sodium resources are far more abundant than lithium resources, more widely distributed, and much cheaper than lithium, so sodium batteries have become a new generation of electrochemical systems with great potential to replace lithium batteries. Similar to lithium batteries, when sodium batteries are charged for the first time, a solid electrolyte interface (SEI) film will be formed on the surface of the negative electrode, and this process will irreversibly consume the active sodium of the positive electrode, thereby reducing the first discharge capacity and the first coulomb efficiency of the battery. Sodium supplementation of the positive electrode is one of the effective methods to solve the above problems. However, the positive electrode sodium supplement currently used has problems such as poor capacity performance and low capacity utilization. The above statements are only used to provide background technology information related to the present application, and do not necessarily constitute the prior art. Summary of the invention
[0003] The present application provides a composite sodium supplement material and a preparation method thereof, a positive electrode plate, a battery and an electrical device. The composite sodium supplement material has a low oxidation potential, a high theoretical capacity and a high capacity utilization rate.
[0004] In a first aspect, the present application provides a composite sodium-supplementing material, comprising a substrate and a carbon coating layer located on at least a portion of the surface of the substrate, wherein the substrate comprises a sodium-supplementing material, and the carbon coating layer comprises an inorganic carbon material and an organic carbonized material.
[0005] The sodium supplement material includes one or more compounds represented by formula (I) and formula (II),
[0006]
[0007] m represents an integer of 1 to 8, and n represents an integer of 2 to 20.
[0008] The composite sodium supplement material provided in the embodiment of the present application may have a low oxidation potential, a high theoretical capacity and a high capacity utilization rate. When applied to the positive electrode of the battery, it will not change the potential of the positive electrode active material, and can improve the battery's first discharge capacity and first coulomb efficiency, and can also make the battery have a high energy density. In addition, the active sodium will gradually be consumed during the battery cycle, and the composite sodium supplement material can also provide excess active sodium to be stored in the negative electrode, thereby compensating for the loss of active sodium during the battery cycle, thereby reducing the probability of excessive release of sodium ions in the positive electrode active material, and further improving the structural stability of the positive electrode active material, and improving the battery's cycle stability and cycle life.
[0009] In any embodiment, the mass of the sodium supplement material is recorded as m1, the mass of the inorganic carbon material is recorded as m2, and the mass of the organic carbonized material is recorded as m3, m1:m2 is (1-4):1, which can be optionally (1-2):1; and / or, m3:(m1+m2) is (0.5-3):100, which can be optionally (1-2):100.
[0010] By adjusting m1:m2 within the above range, it is beneficial to improve the electronic conductivity of the sodium supplement material, reduce the charge transfer resistance and polarization resistance of the sodium supplement material, thereby helping to reduce the oxidation potential of the sodium supplement material, and also beneficial to exert the capacity of the sodium supplement material and improve the capacity utilization of the sodium supplement material.
[0011] By adjusting m3:(m1+m2) within the above range, it is beneficial to improve the uniformity of the carbon coating layer, thereby helping to improve the electronic conductivity of the sodium-supplementing material, reduce the charge transfer resistance and polarization resistance of the sodium-supplementing material, thereby helping to reduce the oxidation potential of the sodium-supplementing material, and also helping to exert the capacity of the sodium-supplementing material and improve the capacity utilization of the sodium-supplementing material.
[0012] In any embodiment, the powder resistivity of the composite sodium supplement material at 25° C. and 20 MPa is 0.2Ω.cm-2Ω.cm, and can be optionally 0.4Ω.cm-1Ω.cm.
[0013] In any embodiment, the specific surface area of the composite sodium supplement material is 3.8 m 2 / g-7.1m 2 / g, optional 4.5m 2 / g-6.8m 2 / g.
[0014] In any embodiment, the volume distribution particle size Dv50 of the composite sodium supplement material is 0.5 μm-10 μm, and can be optionally 1.5 μm-7.6 μm. When the volume distribution particle size Dv50 of the composite sodium supplement material is within the above range, the composite sodium supplement material can have a lower oxidation potential, which is beneficial to exert the capacity of the sodium supplement material and improve the capacity utilization rate of the sodium supplement material.
[0015] In any embodiment, the inorganic carbon material includes one or more of conductive carbon black, conductive graphite, Ketjen black, acetylene black, carbon fiber, carbon nanotube, graphene, and reduced graphene oxide.
[0016] In any embodiment, the organic carbon source forming the organic carbonized material includes one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin, cyclodextrin, polyacrylonitrile, polyethylene glycol, polyvinyl alcohol, polyaniline, polypyrrole, polythiophene, phenolic resin, and epoxy resin.
[0017] In any embodiment, the sodium supplement material includes one or more of the following compounds:
[0018]
[0019]
[0020] The second aspect of the present application provides a method for preparing a composite sodium-supplementing material, comprising the following steps: mixing a sodium-supplementing material, an inorganic carbon material, and an organic carbon source to obtain a mixture, and sintering the obtained mixture at a preset temperature and a preset time to obtain a composite sodium-supplementing material.
[0021] The sodium supplement material includes one or more compounds represented by formula (I) and formula (II),
[0022]
[0023] m represents an integer of 1 to 8, and n represents an integer of 2 to 20.
[0024] The composite sodium supplement material prepared by the preparation method provided in the embodiment of the present application can have a low oxidation potential, a high theoretical capacity and a high capacity utilization rate. When applied to the positive electrode of the battery, it will not change the potential of the positive electrode active material, and can improve the battery's first discharge capacity and first coulomb efficiency, and can also make the battery have a high energy density. In addition, the active sodium will gradually be consumed during the battery cycle, and the composite sodium supplement material can also provide excess active sodium to be stored in the negative electrode, thereby compensating for the loss of active sodium during the battery cycle, thereby reducing the probability of excessive release of sodium ions in the positive electrode active material, and further improving the structural stability of the positive electrode active material, and improving the battery's cycle stability and cycle life.
[0025] In any embodiment, the preset temperature is 350° C.-500° C., and can be optionally 380° C.-480° C. The preset temperature during sintering treatment is within the above range, which can, on the one hand, carbonize the organic carbon source and form a uniform carbon coating layer with high electronic conductivity on the surface of the sodium supplement material matrix together with the inorganic carbon material, and on the other hand, reduce the decomposition of the sodium supplement material.
[0026] In any embodiment, the preset time is 2h-5h, and can be optionally 2.5h-4h. The preset time during the sintering treatment is within the above range, which can, on the one hand, carbonize the organic carbon source and form a uniform carbon coating layer with high electronic conductivity on the surface of the sodium supplement material matrix together with the inorganic carbon material, and on the other hand, reduce the decomposition of the sodium supplement material.
[0027] In any embodiment, the step of mixing the sodium-supplementing material, the inorganic carbon material, and the organic carbon source to obtain a mixture includes the following steps: grinding the sodium-supplementing material and the inorganic carbon material using a dry grinding process to obtain an intermediate, and then mixing the obtained intermediate with an organic carbon source for a second dry grinding to obtain a mixture.
[0028] After the sodium-supplementing material and the inorganic carbon material are ground by dry grinding, the particle size of the sodium-supplementing material can be reduced on the one hand, and the dispersibility of the inorganic carbon material on the surface of the sodium-supplementing material particles can be improved on the other hand, and the contact sites between the inorganic carbon material and the sodium-supplementing material particles can be increased. In addition, after the sodium-supplementing material and the inorganic carbon material are ground by dry grinding, the agglomeration of the inorganic carbon material can be reduced, and the problem of rapid grain growth of the sodium-supplementing material particles during the sintering process can be limited.
[0029] In any embodiment, in the step of grinding the sodium-supplementing material and the inorganic carbon material by a dry grinding process to obtain an intermediate, the grinding time is 0.5h-5h, and can be optionally 0.6h-3h.
[0030] In any embodiment, in the step of grinding the sodium-supplementing material and the inorganic carbon material by dry grinding process to obtain an intermediate, the grinding speed is 200r / min-600r / min, and can be optionally 300r / min-500r / min.
[0031] In any embodiment, in the step of grinding the sodium supplement material and the inorganic carbon material by dry grinding to obtain an intermediate, the volume distribution particle size Dv50 of the intermediate obtained is less than or equal to 20 μm, and can be optionally 1.5 μm-10 μm.
[0032] In any embodiment, in the step of grinding the sodium-supplementing material and the inorganic carbon material by a dry grinding process to obtain an intermediate, the grinding is carried out in a ball mill.
[0033] In any embodiment, in the step of mixing the obtained intermediate with an organic carbon source for a second dry grinding, the grinding time is 0.5h-4h, and optionally 0.6h-2h.
[0034] In any embodiment, in the step of mixing the obtained intermediate with the organic carbon source for a second dry grinding, the grinding speed is 200 r / min-600 r / min, and can be optionally 300 r / min-500 r / min.
[0035] In any embodiment, the preparation method further comprises the steps of grinding and screening the composite sodium supplement material obtained by sintering at a preset temperature and a preset time, thereby reducing the oxidation potential of the composite sodium supplement material, and also facilitating the utilization of the capacity of the sodium supplement material and improving the capacity utilization rate of the sodium supplement material.
[0036] In any embodiment, the mass of the sodium-supplementing material is recorded as m1, the mass of the inorganic carbon material is recorded as m2, the mass of the residual carbon sintered by the organic carbon source at a preset temperature and a preset time is recorded as m3, m1:m2 is (1-4):1, which can be optionally (1-2):1; and / or, m3:(m1+m2) is (0.5-3):100, which can be optionally (1-2):100.
[0037] By adjusting m1:m2 within the above range, it is beneficial to improve the electronic conductivity of the sodium supplement material, reduce the charge transfer resistance and polarization resistance of the sodium supplement material, thereby helping to reduce the oxidation potential of the sodium supplement material, and also beneficial to exert the capacity of the sodium supplement material and improve the capacity utilization of the sodium supplement material.
[0038] By adjusting m3:(m1+m2) within the above range, it is beneficial to improve the uniformity of the carbon coating layer, thereby helping to improve the electronic conductivity of the sodium-supplementing material, reduce the charge transfer resistance and polarization resistance of the sodium-supplementing material, thereby helping to reduce the oxidation potential of the sodium-supplementing material, and also helping to exert the capacity of the sodium-supplementing material and improve the capacity utilization of the sodium-supplementing material.
[0039] In any embodiment, the inorganic carbon material includes one or more of conductive carbon black, conductive graphite, Ketjen black, acetylene black, carbon fiber, carbon nanotube, graphene, and reduced graphene oxide.
[0040] In any embodiment, the specific surface area of the inorganic carbon material is 20 m 2 / g-1600m 2 / g, optional 60m 2 / g-1500m 2 / g. Grinding an inorganic carbon material with a high specific surface area with a sodium supplement material can increase the contact sites between the inorganic carbon material and the sodium supplement material particles, thereby reducing the charge transfer resistance and polarization resistance of the sodium supplement material, thereby reducing the oxidation potential of the sodium supplement material, which is beneficial to exerting the capacity of the sodium supplement material and improving the capacity utilization of the sodium supplement material.
[0041] In any embodiment, the organic carbon source includes one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin, cyclodextrin, polyacrylonitrile, polyethylene glycol, polyvinyl alcohol, polyaniline, polypyrrole, polythiophene, phenolic resin, and epoxy resin.
[0042] In any embodiment, the sodium supplement material includes one or more of the following compounds:
[0043]
[0044] The third aspect of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer comprises the composite sodium supplement material of the first aspect of the present application or the composite sodium supplement material prepared by the preparation method of the second aspect of the present application. This can improve the first discharge capacity and first coulomb efficiency of the battery, and can also make the battery have a high energy density.
[0045] In any embodiment, the weight content of the composite sodium supplement material in the positive electrode film layer is 0.1%-5%, and optionally 0.5%-3%, based on the total weight of the positive electrode film layer. This can further improve the initial discharge capacity and initial coulombic efficiency of the battery, and can also make the battery have a high energy density.
[0046] In any embodiment, the positive electrode film layer further includes a positive electrode active material, and the positive electrode active material includes one or more of layered transition metal oxides, polyanion materials, and Prussian materials.
[0047] A fourth aspect of the present application provides a battery, comprising the positive electrode plate of the third aspect of the present application.
[0048] In any embodiment, the battery includes one or more of a sodium ion battery, a sodium metal battery, and a negative electrode-free sodium battery.
[0049] A fifth aspect of the present application provides an electrical device, comprising the battery of the fourth aspect of the present application, wherein the battery is used to provide electrical energy.
[0050] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0052] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.
[0053] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.
[0054] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.
[0055] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0056] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0057] Figure 6 It is a schematic diagram of an embodiment of an electrical device including the battery of the present application as a power source.
[0058] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 battery cell, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION
[0059] Hereinafter, the composite sodium supplement material and its preparation method, positive electrode plate, battery and electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0060] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0061] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0062] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0063] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0064] In the present application, the terms "plurality" and "multiple" refer to two or more.
[0065] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.
[0066] Unless otherwise specified, the values of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.
[0067] The powder resistivity of a material is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, the test can be performed with reference to GB / T 32993-2016. The test temperature is 25°C and the test pressure is 200 MPa.
[0068] The specific surface area of a material is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured by using the nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be measured using the ASAP 3020 surface area and pore size analyzer from Micromeritics, USA.
[0069] The volume distribution particle size Dv50 of the material is well known in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods well known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to GB / T19077-2016. The test instrument can be the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.
[0070] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.
[0071] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the embodiments of the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.
[0072] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a case and battery cells, and the battery cells or battery modules are accommodated in the case. In some embodiments, the case may serve as part of the chassis structure of the vehicle. For example, part of the case may become at least a part of the floor of the vehicle, or part of the case may become at least a part of the crossbeam and longitudinal beam of the vehicle.
[0073] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.
[0074] A battery cell generally includes an electrode assembly and an electrolyte. The electrode assembly generally includes a positive electrode sheet and a negative electrode sheet. The electrode assembly may be a wound structure or a laminated structure, which is not limited in the present application.
[0075] The battery cell may also include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0076] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0077] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0078] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0079] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0080] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.
[0081] The battery provided in the embodiments of the present application is a sodium battery, which may include, for example, a sodium ion battery, a sodium metal battery, a negative electrode-free sodium metal battery, etc., but the embodiments of the present application are not limited to this.
[0082] A negative electrode-free sodium metal battery generally refers to a battery that is formed by not actively setting a negative electrode active material layer on the negative electrode side during the manufacturing process of the battery, for example, a sodium metal layer is not set at the negative electrode through processes such as coating or deposition, or a negative electrode active material layer is formed by a carbonaceous active material layer during the manufacturing process of the battery. During the first charge, the sodium ions obtain electrons on the negative electrode side and deposit on the surface of the negative electrode current collector to form metallic sodium. During discharge, the metallic sodium can be converted into sodium ions and return to the positive electrode to achieve cyclic charge and discharge. Compared with other batteries, a negative electrode-free sodium metal battery can obtain a higher energy density because it has no negative electrode active material layer. In some embodiments, in order to improve battery performance, some conventional substances that can be used as negative electrode active materials, such as carbon materials, can also be set on the negative electrode side of the negative electrode-free sodium metal battery. Although these substances have a certain capacity, due to their low content and not being used as the main negative electrode active material in the battery, the battery thus constructed can still be regarded as a negative electrode-free sodium metal battery. The CB (Cell Balance) value of the negative electrode-free sodium metal battery is usually very small. For example, in some embodiments, the CB value of the negative electrode-free sodium metal battery can be less than or equal to 0.1. The CB value is the unit area capacity of the negative electrode in the battery divided by the unit area capacity of the positive electrode. Since the negative electrode-free sodium metal battery does not contain or contains only a small amount of negative electrode active material, the unit area capacity of the negative electrode is small, and thus the CB value is very small, for example, usually less than or equal to 0.1.
[0083] The embodiment of the present application provides a composite sodium supplement material.
[0084] The composite sodium supplement material comprises a substrate and a carbon coating layer located on at least a portion of the surface of the substrate. The substrate comprises a sodium supplement material, and the carbon coating layer comprises an inorganic carbon material and an organic carbonized material.
[0085] The sodium supplement material includes one or more compounds represented by formula (I) and formula (II),
[0086]
[0087] m represents an integer of 1 to 8, and n represents an integer of 2 to 20.
[0088] The composite sodium supplement material provided in the embodiment of the present application includes a substrate and a carbon coating layer located on at least a portion of the surface of the substrate.
[0089] When the battery is charged for the first time (i.e., the first charge in the formation stage), the sodium supplement material matrix decomposes and releases active sodium ions and gases. The released active sodium ions can make up for the loss of active sodium ions caused by the formation of the SEI film at the negative electrode, thereby improving the battery's first discharge gram capacity and first coulomb efficiency; the gas released by the decomposition of the sodium supplement material matrix can be removed in the battery formation stage.
[0090] The sodium supplement material includes one or more of the compounds shown in formula (I) and formula (II), so the sodium supplement material can have the advantages of high decomposition rate and high theoretical capacity. However, the sodium supplement material shown in formula (I) and formula (II) has a high oxidation potential, low actual capacity when used in the battery, and low capacity utilization, which may affect the performance of the positive electrode active material in the battery and may also reduce the energy density of the battery.
[0091] Inorganic carbon materials have high electronic conductivity, and coating them on the surface of the sodium-supplementing material matrix can improve the electronic conductivity of the sodium-supplementing material matrix; however, inorganic carbon materials are easy to agglomerate, so the carbon coating layer formed by the inorganic carbon materials on the surface of the sodium-supplementing material matrix is usually uneven, which is not conducive to reducing the oxidation potential of the sodium-supplementing material, nor is it conducive to the capacity of the sodium-supplementing material.
[0092] The organic carbonized material is obtained by carbonizing an organic carbon source. The organic carbon source will soften first after being heated, and thus can form a uniform coating with the inorganic carbon material to coat the surface of the sodium supplement material particles; after the carbonization treatment, the organic carbon source in the coating finally forms an organic carbonized material. And after the carbonization treatment, a uniform carbon coating layer with high electronic conductivity can be formed on the surface of the sodium supplement material matrix, thereby improving the electronic conductivity of the sodium supplement material, reducing the charge transfer resistance and polarization resistance of the sodium supplement material, and then reducing the oxidation potential of the sodium supplement material, which is also beneficial to exert the capacity of the sodium supplement material and improve the capacity utilization rate of the sodium supplement material.
[0093] Therefore, the composite sodium supplement material provided in the embodiment of the present application can have a low oxidation potential, a high theoretical capacity and a high capacity utilization rate. When applied to the positive electrode of the battery, it will not change the potential of the positive electrode active material, and can improve the battery's first discharge capacity and first coulomb efficiency, and can also make the battery have a high energy density. In addition, the active sodium will gradually be consumed during the battery cycle, and the composite sodium supplement material can also provide excess active sodium to be stored in the negative electrode, thereby compensating for the loss of active sodium during the battery cycle, thereby reducing the probability of excessive release of sodium ions in the positive electrode active material, thereby improving the structural stability of the positive electrode active material, and improving the battery's cycle stability and cycle life.
[0094] The mass of the sodium supplement material is recorded as m1, the mass of the inorganic carbon material is recorded as m2, and the mass of the organic carbonized material is recorded as m3.
[0095] In some embodiments, m1:m2 may be (1-4):1, and may be (1-2):1. By adjusting m1:m2 within the above range, it is beneficial to improve the electronic conductivity of the sodium supplement material, reduce the charge transfer resistance and polarization resistance of the sodium supplement material, thereby reducing the oxidation potential of the sodium supplement material, and also beneficial to exert the capacity of the sodium supplement material and improve the capacity utilization rate of the sodium supplement material.
[0096] In some embodiments, m3:(m1+m2) can be (0.5-3):100, and can be optionally (1-2):100. By adjusting m3:(m1+m2) within the above range, it is beneficial to improve the uniformity of the carbon coating layer, thereby improving the electronic conductivity of the sodium supplement material, reducing the charge transfer resistance and polarization resistance of the sodium supplement material, thereby reducing the oxidation potential of the sodium supplement material, and also beneficial to exerting the capacity of the sodium supplement material and improving the capacity utilization of the sodium supplement material.
[0097] The mass content of organic carbonized materials in the composite sodium supplement material can be obtained by high-frequency infrared carbon-sulfur analysis. The test standard can refer to GB / T 20123-2006.
[0098] In some embodiments, the powder resistivity of the composite sodium supplement material at 25° C. and 20 MPa may be 0.2Ω.cm-2Ω.cm, or optionally 0.4Ω.cm-1Ω.cm.
[0099] In some embodiments, the specific surface area of the composite sodium supplement material can be 3.8 m 2 / g-7.1m 2 / g, optional 4.5m 2 / g-6.8m 2 / g.
[0100] In some embodiments, the volume distribution particle size Dv50 of the composite sodium supplement material can be 0.5 μm-10 μm, and can be optionally 1.5 μm-7.6 μm. When the volume distribution particle size Dv50 of the composite sodium supplement material is within the above range, the composite sodium supplement material can have a lower oxidation potential, which is beneficial to exert the capacity of the sodium supplement material and improve the capacity utilization rate of the sodium supplement material.
[0101] In some embodiments, the inorganic carbon material may include, but is not limited to, one or more of conductive carbon black, conductive graphite, Ketjen black, acetylene black, carbon fiber, carbon nanotube, graphene, and reduced graphene oxide.
[0102] In some embodiments, the organic carbon source forming the organic carbonized material may include, but is not limited to, one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin, cyclodextrin, polyacrylonitrile, polyethylene glycol, polyvinyl alcohol, polyaniline, polypyrrole, polythiophene, phenolic resin, and epoxy resin.
[0103] In some embodiments, m may represent an integer from 1 to 6, optionally an integer from 1 to 4, and more optionally 1 or 2.
[0104] In some embodiments, n may represent an integer from 2 to 10, optionally an integer from 2 to 6, and more optionally 2 or 3.
[0105] In some embodiments, the sodium supplement material may include, but is not limited to, one or more of the following compounds:
[0106]
[0107]
[0108] [Preparation method]
[0109] The present application also provides a method for preparing a composite sodium supplement material.
[0110] The preparation method comprises the following steps: mixing a sodium supplement material, an inorganic carbon material and an organic carbon source to obtain a mixture, and sintering the obtained mixture at a preset temperature and a preset time to obtain a composite sodium supplement material.
[0111] The sodium supplement material includes one or more compounds represented by formula (I) and formula (II),
[0112]
[0113] m represents an integer of 1 to 8, and n represents an integer of 2 to 20.
[0114] The preparation method of the composite sodium supplement material provided in the embodiment of the present application is simple in process and suitable for large-scale production.
[0115] When the battery is charged for the first time (i.e., the first charge in the formation stage), the sodium supplement material matrix decomposes and releases active sodium ions and gases. The released active sodium ions can make up for the loss of active sodium ions caused by the formation of the SEI film at the negative electrode, thereby improving the battery's first discharge capacity and first coulomb efficiency; the gas released by the decomposition of the sodium supplement material matrix can be removed in the battery formation stage. The sodium supplement material includes one or more of the compounds shown in formula (I) and formula (II), so the sodium supplement material can have the advantages of high decomposition rate and high theoretical capacity. However, the sodium supplement materials shown in formula (I) and formula (II) have high oxidation potentials, low actual capacity when used in batteries, and low capacity utilization, which may affect the performance of the positive electrode active material in the battery and may also reduce the energy density of the battery.
[0116] Inorganic carbon materials have high electronic conductivity, and coating them on the surface of the sodium-supplementing material matrix can improve the electronic conductivity of the sodium-supplementing material matrix; however, inorganic carbon materials are easy to agglomerate, so the carbon coating layer formed by the inorganic carbon materials on the surface of the sodium-supplementing material matrix is usually uneven, which is not conducive to reducing the oxidation potential of the sodium-supplementing material, nor is it conducive to the capacity of the sodium-supplementing material.
[0117] In the embodiment of the present application, a mixture including a sodium supplement material, an inorganic carbon material, and an organic carbon source is sintered together at a preset temperature and a preset time. The organic carbon source will soften first after being heated, thereby forming a uniform coating together with the inorganic carbon material to coat the surface of the sodium supplement material particles; after sintering, the organic carbon source in the coating eventually forms an organic carbonized material. Moreover, after sintering, a uniform carbon coating layer with high electronic conductivity can be formed on the surface of the sodium supplement material matrix, thereby improving the electronic conductivity of the sodium supplement material, reducing the charge transfer resistance and polarization resistance of the sodium supplement material, and further reducing the oxidation potential of the sodium supplement material, which is also beneficial to exerting the capacity of the sodium supplement material and improving the capacity utilization rate of the sodium supplement material.
[0118] Therefore, the composite sodium supplement material prepared by the preparation method provided in the embodiment of the present application can have a low oxidation potential, a high theoretical capacity and a high capacity utilization rate. When applied to the positive electrode of the battery, it will not change the potential of the positive electrode active material, and can improve the battery's first discharge capacity and first coulomb efficiency, and can also make the battery have a high energy density. In addition, the active sodium will gradually be consumed during the battery cycle, and the composite sodium supplement material can also provide excess active sodium to be stored in the negative electrode, thereby compensating for the loss of active sodium during the battery cycle, thereby reducing the probability of excessive release of sodium ions in the positive electrode active material, and further improving the structural stability of the positive electrode active material, and improving the battery's cycle stability and cycle life.
[0119] In some embodiments, m may represent an integer from 1 to 6, optionally an integer from 1 to 4, and more optionally 1 or 2.
[0120] In some embodiments, n may represent an integer from 2 to 10, optionally an integer from 2 to 6, and more optionally 2 or 3.
[0121] In some embodiments, the sodium supplement material may include, but is not limited to, one or more of the following compounds:
[0122]
[0123] In some embodiments, the preset temperature may be 350° C.-500° C., and may be 380° C.-480° C. The preset temperature during sintering treatment is within the above range, which can, on the one hand, carbonize the organic carbon source and form a uniform carbon coating layer with high electronic conductivity on the surface of the sodium supplementing material matrix together with the inorganic carbon material, and on the other hand, reduce the decomposition of the sodium supplementing material.
[0124] In some embodiments, the preset time can be 2h-5h, and can be optionally 2.5h-4h. The preset time during the sintering treatment is within the above range. On the one hand, the organic carbon source can be carbonized and form a uniform carbon coating layer with high electronic conductivity on the surface of the sodium supplement material matrix together with the inorganic carbon material. On the other hand, the decomposition of the sodium supplement material can also be reduced.
[0125] In some embodiments, the step of mixing the sodium-supplementing material, the inorganic carbon material, and the organic carbon source to obtain a mixture includes the following steps: grinding the sodium-supplementing material and the inorganic carbon material using a dry grinding process to obtain an intermediate, and then mixing the obtained intermediate with the organic carbon source for a second dry grinding to obtain a mixture.
[0126] The particle size of the currently commercially available sodium supplement materials is usually relatively large, and there may be problems of residue or reduced capacity utilization when used directly. The manufacturing cost of small particles and nano-level sodium supplement materials is high, which is not conducive to large-scale production. Therefore, after the sodium supplement material and the inorganic carbon material are ground by a dry grinding process, on the one hand, the particle size of the sodium supplement material can be reduced, and on the other hand, the dispersibility of the inorganic carbon material on the surface of the sodium supplement material particles can be improved, and the contact sites between the inorganic carbon material and the sodium supplement material particles can be increased. In addition, after the sodium supplement material and the inorganic carbon material are ground by a dry grinding process, the agglomeration of the inorganic carbon material can also be reduced, and the problem of rapid grain growth of the sodium supplement material particles during the sintering process can also be limited.
[0127] In some embodiments, in the step of grinding the sodium-supplementing material and the inorganic carbon material by a dry grinding process to obtain an intermediate, the grinding time can be 0.5h-5h, and can be optionally 0.6h-3h.
[0128] In some embodiments, in the step of grinding the sodium-supplementing material and the inorganic carbon material by dry grinding to obtain an intermediate, the grinding speed can be 200 r / min-600 r / min, and can be optionally 300 r / min-500 r / min.
[0129] In the step of grinding the sodium supplement material and the inorganic carbon material by dry grinding to obtain an intermediate, the volume distribution particle size of the intermediate obtained can be adjusted by adjusting the grinding time and / or the grinding speed.
[0130] In some embodiments, in the step of grinding the sodium supplement material and the inorganic carbon material by dry grinding to obtain an intermediate, the volume distribution particle size Dv50 of the intermediate obtained can be less than or equal to 20 μm, and can be 1.5 μm-10 μm, 1.5 μm-7 μm. This is conducive to reducing the oxidation potential of the sodium supplement material and improving the capacity utilization rate of the sodium supplement material.
[0131] The volume distribution particle size Dv50 of the intermediate refers to the volume distribution particle size Dv50 of the sodium supplement material after grinding.
[0132] In some embodiments, in the step of grinding the sodium-supplementing material and the inorganic carbon material by a dry grinding process to obtain an intermediate, the grinding can be performed in a ball mill.
[0133] In some embodiments, in the step of mixing the obtained intermediate with the organic carbon source for a second dry grinding, the grinding time may be 0.5 h-4 h, and optionally 0.6 h-2 h.
[0134] In some embodiments, in the step of mixing the obtained intermediate with the organic carbon source for a second dry grinding, the grinding speed may be 200 r / min-600 r / min, and may be optionally 300 r / min-500 r / min.
[0135] In some embodiments, the preparation method may further include the step of grinding and screening the composite sodium supplement material obtained by sintering at a preset temperature and a preset time, thereby reducing the oxidation potential of the composite sodium supplement material, and also facilitating the utilization of the capacity of the sodium supplement material and improving the capacity utilization rate of the sodium supplement material.
[0136] In some embodiments, the inorganic carbon material may include, but is not limited to, one or more of conductive carbon black, conductive graphite, Ketjen black, acetylene black, carbon fiber, carbon nanotube, graphene, and reduced graphene oxide.
[0137] In some embodiments, the specific surface area of the inorganic carbon material can be 20 m 2 / g-1600m 2 / g, optional 60m 2 / g-1500m 2 / g. Grinding an inorganic carbon material with a high specific surface area with a sodium supplement material can increase the contact sites between the inorganic carbon material and the sodium supplement material particles, thereby reducing the charge transfer resistance and polarization resistance of the sodium supplement material, thereby reducing the oxidation potential of the sodium supplement material, which is beneficial to exerting the capacity of the sodium supplement material and improving the capacity utilization of the sodium supplement material.
[0138] In some embodiments, the organic carbon source may include, but is not limited to, one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin, cyclodextrin, polyacrylonitrile, polyethylene glycol, polyvinyl alcohol, polyaniline, polypyrrole, polythiophene, phenolic resin, and epoxy resin.
[0139] The mass of the sodium supplement material is recorded as m1, the mass of the inorganic carbon material is recorded as m2, and the mass of the residual carbon after the organic carbon source is sintered at the corresponding preset temperature and preset time is recorded as m3. The mass of the residual carbon after the organic carbon source is sintered at the corresponding preset temperature and preset time is related to the type of the organic carbon source. By selecting a suitable organic carbon source and selecting a suitable sintering treatment temperature and / or time, the residual carbon mass m3 of the organic carbon source can be adjusted.
[0140] In some embodiments, m1:m2 may be (1-4):1, and may be (1-2):1. By adjusting m1:m2 within the above range, it is beneficial to improve the electronic conductivity of the sodium supplement material, reduce the charge transfer resistance and polarization resistance of the sodium supplement material, thereby reducing the oxidation potential of the sodium supplement material, and also beneficial to exert the capacity of the sodium supplement material and improve the capacity utilization rate of the sodium supplement material.
[0141] In some embodiments, m3:(m1+m2) can be (0.5-3):100, and can be optionally (1-2):100. By adjusting m3:(m1+m2) within the above range, it is beneficial to improve the uniformity of the carbon coating layer, thereby improving the electronic conductivity of the sodium supplement material, reducing the charge transfer resistance and polarization resistance of the sodium supplement material, thereby reducing the oxidation potential of the sodium supplement material, and also beneficial to exerting the capacity of the sodium supplement material and improving the capacity utilization of the sodium supplement material.
[0142] Unless otherwise specified, all raw materials used in the above preparation method can be obtained from the market.
[0143] [Positive electrode]
[0144] The embodiment of the present application also provides a positive electrode plate.
[0145] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer located on at least one surface of the positive electrode current collector. The positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is located on any one or both of the two opposite surfaces of the positive electrode current collector.
[0146] The positive electrode film layer includes the composite sodium supplement material or the composite sodium supplement material prepared by the above-mentioned preparation method, thereby improving the first discharge capacity and first coulomb efficiency of the battery, and also making the battery have a high energy density.
[0147] In some embodiments, the weight content of the composite sodium supplement material in the positive electrode film layer is 0.1%-5%, and optionally 0.5%-3%, based on the total weight of the positive electrode film layer. This can further improve the first discharge capacity and first coulomb efficiency of the battery, and can also make the battery have a high energy density.
[0148] The positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes a material capable of extracting and embedding sodium. As an example, the positive electrode active material may be one or more of a layered transition metal oxide (including but not limited to P2 type, O3 type, etc.), a polyanion material (such as phosphate, fluorophosphate, pyrophosphate, sulfate, etc.), and a Prussian material.
[0149] In some embodiments, as examples, the positive electrode active material may include but is not limited to NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, Na 0.67 MO2 (M includes at least two of Fe, Co, Cr, Mn, Ni, V, Ti, and Mo), NaMO2 (M includes at least two of Fe, Co, Ni, V, Ti, and Mo), NaFePO4, NaMnPO4, NaCoPO4, Na4Fe3(PO4)2O7, Na3V2(PO4)2F3, Na3V2(PO4)3, Prussian blue, Prussian white, and one or more of their respective modified compounds.
[0150] The modified compounds of the above-mentioned positive electrode active materials may be the ones that undergo doping modification and / or surface coating modification on the positive electrode active materials.
[0151] In some embodiments, the positive electrode film layer may also optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0152] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylic resin, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) One or more.
[0153] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0154] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, the optional positive electrode conductive agent, the optional positive electrode binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0155] [Negative electrode]
[0156] The battery cell includes a negative electrode plate. The structure and composition of the negative electrode plate can be selected according to the type of the battery cell, and the embodiment of the present application is not limited to this.
[0157] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0158] The negative electrode active material may be a material known in the art. For example, the negative electrode active material includes but is not limited to one or more of soft carbon, hard carbon, and mesophase micro carbon beads.
[0159] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0160] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. As an example, the negative electrode binder may include, butadiene styrene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) or more.
[0161] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.
[0162] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0163] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate may also include a protective layer covering the surface of the negative electrode film layer.
[0164] In some embodiments, the negative electrode plate may include a negative electrode current collector and a metal layer disposed on at least one surface of the negative electrode current collector. The metal material in the metal layer may include but is not limited to one or more of sodium element and sodium alloy.
[0165] The sodium alloy may be an alloy formed by metallic sodium and other metallic elements or non-metallic elements. As an example, the other metallic elements in the sodium alloy may include, but are not limited to, one or more of tin, zinc, aluminum, magnesium, silver, gold, gallium, indium, and platinum, and the non-metallic elements in the sodium alloy may include one or more of boron, carbon, and silicon.
[0166] In some embodiments, the negative electrode plate may be a sodium plate (foil) or a sodium alloy plate (foil).
[0167] In some embodiments, the negative electrode sheet may include a negative electrode current collector to assemble into a negative electrode-free sodium metal battery cell.
[0168] In some embodiments, the negative electrode current collector may include a metal foil, a three-dimensional porous current collector, or a composite current collector. As an example of a metal foil, copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, and aluminum alloy foil may be used. As an example of a three-dimensional porous current collector, copper mesh, nickel mesh, foam copper, foam nickel, and foam aluminum may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0169] [Electrolytes]
[0170] The battery cell includes an electrolyte. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can include one or more selected from solid electrolytes and liquid electrolytes (ie, electrolytes).
[0171] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0172] In some embodiments, as an example, the electrolyte salt may include, but is not limited to, one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP), and sodium tetrafluorooxalatophosphate (NaTFOP).
[0173] In some embodiments, the solvent may include, but is not limited to, one or more of an ester solvent, a sulfone solvent, and an ether solvent. As an example, the solvent may include, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), and one or more of ethylene glycol dimethyl ether (DME).
[0174] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance.
[0175] [Isolation film]
[0176] Battery cells using electrolytes and some battery cells using solid electrolytes also include a separator, which is disposed between the positive electrode sheet and the negative electrode sheet and mainly serves to prevent internal short circuits.
[0177] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0178] In some embodiments, the material of the isolation membrane may include, but is not limited to, one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0179] The preparation method of battery cells is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected after drying. After packaging, standing, formation and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.
[0180] Electrical devices
[0181] The embodiment of the present application also provides an electrical device, which includes a battery provided in the embodiment of the present application, and the battery is used to provide electrical energy. The battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0182] The electrical device can select a specific type of battery, such as a battery cell, a battery module or a battery pack, according to its usage requirements.
[0183] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0184] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0185] Example
[0186] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations can be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0187] Example 1
[0188] The sodium oxalate (compound H1) with a volume distribution particle size of 16 μm and the inorganic carbon material conductive carbon black (with a specific surface area of 60 m 2 / g) was dry ground for the first time in a grinding jar at a grinding speed of 450r / min and a grinding time of 3h to obtain an intermediate with a volume distribution particle size Dv50 of about 3μm (herein, the volume distribution particle size Dv50 of the sodium oxalate material obtained after the first grinding).
[0189] Glucose powder as an organic carbon source was added to the grinding tank, and dry grinding was performed for the second time at a grinding speed of 400 r / min and a grinding time of 1 h to obtain a mixture.
[0190] The obtained mixture was sintered at 420°C for 3h, and then ground and sieved to obtain a composite sodium supplement material. The volume distribution particle size Dv50 of the composite sodium supplement material was about 3.2μm.
[0191] In the obtained composite sodium-supplementing material, the mass of the sodium-supplementing material matrix is recorded as m1, the mass of the inorganic carbon material is recorded as m2, and the mass of the residual carbon after sintering the organic carbon source at 420°C for 3 hours is recorded as m3. m1:m2 is 2:1, and m3:(m1+m2) is 2:100.
[0192] Examples 2 to 3
[0193] The preparation method of the composite sodium-supplementing material is similar to that of Example 1, except that the grinding speed and / or grinding time of the first dry grinding is adjusted to obtain intermediates with different volume distribution particle sizes Dv50. The volume distribution particle size Dv50 of the obtained intermediates and the volume distribution particle size Dv50 of the composite sodium-supplementing material are shown in Table 1.
[0194] Examples 4 to 7
[0195] The preparation method of the composite sodium supplement material is similar to that of Example 1, except that the temperature of the sintering treatment is different. The specific parameters are shown in Table 1.
[0196] Examples 8 to 12
[0197] The preparation method of the composite sodium supplement material is similar to that of Example 1, except that m1:m2 is different. The specific parameters are shown in Table 1.
[0198] Examples 13 to 16
[0199] The preparation method of the composite sodium supplement material is similar to that of Example 1, except that m3:(m1+m2) is different. The specific parameters are shown in Table 1.
[0200] Examples 17 to 27
[0201] The preparation method of the composite sodium supplement material is similar to that of Example 1, except that the types of the sodium supplement material, the inorganic carbon material and / or the organic carbon source are different. The specific types are detailed in Table 1.
[0202] Compound H1
[0203] Compound H2
[0204] Compound H3
[0205] Compound H4
[0206]
[0207] Comparative Example 1
[0208] Sodium oxalate (compound H1) with a volume distribution particle size Dv50 of 16 μm was used as the sodium supplement material.
[0209] Comparative Example 2
[0210] Sodium oxalate (compound H1) with a volume distribution particle size Dv50 of 16 μm was dry-ground in a grinding jar to obtain sodium oxalate with a volume distribution particle size Dv50 of about 3.2 μm as a sodium supplement material.
[0211] Comparative Example 3
[0212] Sodium oxalate (compound H1), a sodium supplement material with a volume distribution particle size Dv50 of 11.2 μm, and conductive carbon black, an inorganic carbon material, are dry ground in a grinding pot to obtain a mixture with a volume distribution particle size Dv50 of 3.2 μm as a sodium supplement material. The mass of the sodium supplement material is recorded as m1, and the mass of the inorganic carbon material is recorded as m2, and m1:m2 is 4:1.
[0213] Performance Testing
[0214] (1) Oxidation potential test of sodium supplement materials
[0215] The binder polyvinylidene fluoride (PVDF) is fully dissolved in N-methylpyrrolidone (NMP), and then the conductive agent conductive carbon black and the composite sodium supplement material prepared above are added to form a uniform slurry; the slurry is evenly coated on the surface of the aluminum foil, and then transferred to a vacuum drying oven for complete drying, and then rolled and punched to obtain a positive electrode sheet. Taking the total mass of the binder polyvinylidene fluoride, the conductive agent conductive carbon black, and the composite sodium supplement material as 100%, the mass content of the binder polyvinylidene fluoride is 10%, the mass content of the sodium supplement material matrix in the composite sodium supplement material is 50%, and the total mass content of the conductive agent conductive carbon black and the carbon coating layer in the composite sodium supplement material is 40%.
[0216] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), NaPF6 was dissolved in ethylene glycol dimethyl ether DME and stirred evenly to obtain an electrolyte with a concentration of 0.5 mol / L.
[0217] The positive electrode plate, the isolation film (polypropylene film), the sodium plate and the electrolyte are assembled into a button cell.
[0218] At 25°C, the assembled button cell was charged at a constant current of 0.02C to 4.5V, and then charged at a constant voltage of 4.5V to a current of 0.02C to obtain the first charging capacity of the button cell; the button cell was then discharged at a constant current of 0.02C to 1.5V to obtain the first discharge capacity of the button cell.
[0219] The first charge gram capacity of the composite sodium supplement material (mAh / g) = the first charge capacity of the button battery / the mass of the composite sodium supplement material.
[0220] The first discharge capacity in gram of the composite sodium supplement material (mAh / g) = the first discharge capacity of the button cell / the mass of the composite sodium supplement material.
[0221] The corresponding dQ / dV curve is calculated by differentiating the first cycle charge and discharge curve, or the assembled button cell is subjected to cyclic voltammetry (CV) test with a test voltage of 1.5V-4.5V and a scan rate of 0.1mV / s. The voltage corresponding to the oxidation peak is the oxidation potential of the composite sodium supplement material.
[0222] (2) The first coulombic efficiency test of a negative electrode-free sodium metal battery
[0223] The composite sodium supplement material prepared in the above embodiments and comparative examples is mixed with the positive electrode active material Na4Fe3(PO4)2O7, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 2.1:67.9:20:10, and then an appropriate amount of NMP is added and stirred to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the aluminum foil, and then transferred to a vacuum drying oven and dried at 110°C for 5h-6h, and then rolled and punched to obtain a positive electrode sheet.
[0224] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), NaPF6 was dissolved in ethylene glycol dimethyl ether (DME), stirred evenly, and an electrolyte with a concentration of 0.5 mol / L was obtained.
[0225] The positive electrode sheet, isolation film (polypropylene film), and carbon-coated copper foil prepared above are stacked in order to form a stacked electrode assembly, the electrode assembly is placed in an outer package, injected with the electrolyte prepared above, and then subjected to vacuum packaging, standing, formation, shaping and other processes to obtain a negative electrode-free sodium metal battery.
[0226] At 25°C, the negative electrode-free sodium metal battery was charged to 4.2V at a constant current of 1 / 3C, and then charged at a constant voltage of 4.2V to a current of 0.05C to obtain the first charging capacity of the negative electrode-free sodium metal battery; the negative electrode-free sodium metal battery was then discharged to 1.5V at a constant current of 1 / 3C to obtain the first discharge capacity of the negative electrode-free sodium metal battery.
[0227] The first coulombic efficiency of the negative electrode-free sodium metal battery = the first discharge capacity of the negative electrode-free sodium metal battery / the first charge capacity of the negative electrode-free sodium metal battery.
[0228] The test results are shown in Table 2.
[0229] Table 2
[0230]
[0231] It can be seen from the test results in Table 2 that the composite sodium supplement material provided in the embodiments of the present application has low oxidation potential, high capacity and high capacity utilization.
[0232] It can also be seen from the test results in Table 2 that the battery using the composite sodium supplement material provided in the embodiments of the present application has a high first coulombic efficiency.
[0233] Comparative Example 2 adopts the direct grinding method, which can improve the capacity of sodium oxalate to a certain extent, but the improvement effect is limited. At the same time, the oxidation potential of sodium oxalate is still very high. Therefore, when applied to the battery system, the actual capacity of sodium oxalate is still poor, and the first coulombic efficiency of the battery is still low.
[0234] In Comparative Example 3, sodium oxalate is ground together with an inorganic carbon material, thereby increasing the capacity of sodium oxalate. However, the oxidation potential of sodium oxalate is still very high. Therefore, when applied to a battery system, the capacity of sodium oxalate at a high potential cannot be effectively released, resulting in the actual capacity of sodium oxalate still being poor, and the first coulombic efficiency of the battery is still low.
[0235] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A composite sodium supplement material, characterized in that: The composite sodium supplement material comprises a substrate and a carbon coating layer located on at least a portion of the surface of the substrate, wherein the substrate comprises a sodium supplement material, and the carbon coating layer comprises an inorganic carbon material and an organic carbonized material; The sodium supplement material includes one or more compounds represented by formula (I) and formula (II), m represents an integer of 1 to 8, and n represents an integer of 2 to 20.
2. The composite sodium supplement material according to claim 1, characterized in that The mass of the sodium supplement material is recorded as m1, the mass of the inorganic carbon material is recorded as m2, and the mass of the organic carbonized material is recorded as m3. m1:m2 is (1-4):1, and may be (1-2):1; and / or, m3:(m1+m2) is (0.5-3):100, and can be optionally (1-2):
100.
3. The composite sodium supplement material according to any one of claims 1 to 2, characterized in that: The powder resistivity of the composite sodium supplement material at 25°C and 20MPa is 0.2Ω.cm-2Ω.cm, and can be optionally 0.4Ω.cm-1Ω.cm; and / or, The specific surface area of the composite sodium supplement material is 3.8 m 2 / g-7.1m 2 / g, optional 4.5m 2 / g-6.8m 2 / g; and / or, The volume distribution particle size Dv50 of the composite sodium supplement material is 0.5 μm-10 μm, and can be optionally 1.5 μm-7.6 μm.
4. The composite sodium supplement material according to any one of claims 1 to 3, characterized in that: The inorganic carbon material includes one or more of conductive carbon black, conductive graphite, Ketjen black, acetylene black, carbon fiber, carbon nanotube, graphene, and reduced graphene oxide; and / or, The organic carbon source forming the organic carbonized material includes one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin, cyclodextrin, polyacrylonitrile, polyethylene glycol, polyvinyl alcohol, polyaniline, polypyrrole, polythiophene, phenolic resin, and epoxy resin.
5. The composite sodium supplement material according to any one of claims 1 to 4, characterized in that: The sodium supplement material includes one or more of the following compounds:
6. A method for preparing a composite sodium supplement material, characterized in that: The steps include: A sodium supplement material, an inorganic carbon material, and an organic carbon source are mixed to obtain a mixture, wherein: The sodium supplement material includes one or more compounds represented by formula (I) and formula (II), m represents an integer from 1 to 8, and n represents an integer from 2 to 20; The obtained mixture is sintered at a preset temperature and a preset time to obtain a composite sodium supplement material.
7. The preparation method according to claim 6, characterized in that: The preset temperature is 350°C-500°C, and can be optionally 380°C-480°C; and / or, The preset time is 2h-5h, and can be optionally 2.5h-4h.
8. The preparation method according to any one of claims 6 to 7, characterized in that: The step of mixing the sodium supplement material, the inorganic carbon material, and the organic carbon source to obtain a mixture comprises the following steps: The sodium supplement material and the inorganic carbon material are ground by a dry grinding process to obtain an intermediate, and then the intermediate is mixed with an organic carbon source for a second dry grinding to obtain a mixture.
9. The preparation method according to claim 8, characterized in that: In the step of grinding the sodium supplement material and the inorganic carbon material by dry grinding process to obtain an intermediate, Grinding time is 0.5h-5h, optional 0.6h-3h; and / or, The grinding speed is 200r / min-600r / min, and can be 300r / min-500r / min; and / or, The volume distribution particle size Dv50 of the obtained intermediate is less than or equal to 20 μm, and can be optionally 1.5 μm-10 μm; and / or, Grinding is carried out in a ball mill.
10. The preparation method according to any one of claims 8 to 9, characterized in that: In the step of mixing the obtained intermediate with an organic carbon source for a second dry grinding, Grinding time is 0.5h-4h, optional 0.6h-2h; and / or, The grinding speed is 200r / min-600r / min, and can be selected as 300r / min-500r / min.
11. The preparation method according to any one of claims 6 to 10, characterized in that: The preparation method further comprises the steps of: grinding and screening the composite sodium supplement material obtained by sintering at a preset temperature and a preset time.
12. The preparation method according to any one of claims 6 to 11, characterized in that: The mass of the sodium supplement material is recorded as m1, the mass of the inorganic carbon material is recorded as m2, and the mass of the residual carbon after sintering the organic carbon source at a preset temperature and a preset time is recorded as m3. m1:m2 is (1-4):1, and may be (1-2):1; and / or, m3:(m1+m2) is (0.5-3):100, and can be optionally (1-2):
100.
13. The preparation method according to any one of claims 6 to 12, characterized in that: The inorganic carbon material includes one or more of conductive carbon black, conductive graphite, Ketjen black, acetylene black, carbon fiber, carbon nanotube, graphene, and reduced graphene oxide; and / or, The specific surface area of the inorganic carbon material is 20 m 2 / g-1600m 2 / g, optional 60m 2 / g-1500m 2 / g; and / or, The organic carbon source comprises one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin, cyclodextrin, polyacrylonitrile, polyethylene glycol, polyvinyl alcohol, polyaniline, polypyrrole, polythiophene, phenolic resin, epoxy resin; and / or, The sodium supplement material includes one or more of the following compounds:
14. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode film layer comprises the composite sodium-supplementing material according to any one of claims 1 to 5 or the composite sodium-supplementing material prepared by the preparation method according to any one of claims 6 to 13.
15. The positive electrode sheet according to claim 14, characterized in that: The weight content of the composite sodium-supplementing material in the positive electrode film layer is 0.1%-5%, optionally 0.5%-3%, based on the total weight of the positive electrode film layer.
16. The positive electrode sheet according to any one of claims 14 to 15, characterized in that: The positive electrode film layer also includes a positive electrode active material, and the positive electrode active material includes one or more of layered transition metal oxides, polyanion materials, and Prussian materials.
17. A battery, characterized in that: Comprising the positive electrode sheet as described in any one of claims 14-16.
18. The battery according to claim 17, characterized in that The battery includes one or more of a sodium ion battery, a sodium metal battery, and a negative electrode-free sodium battery.
19. An electrical device, characterized in that: A battery comprising any one of claims 17-18, wherein the battery is used to provide electrical energy.
Citation Information
Patent Citations
Sodium ion battery positive electrode containing sodium supplementation additive and preparation method and application thereof
CN110112475A
Thermal repair regeneration method for phosphate electrode material of sodium ion battery
CN114824547A
Sodium-ion battery positive electrode material and preparation method and application thereof
CN116314720A
Preparation method of polyanionic sodium ion battery positive electrode material
CN116314795A
Positive pole piece and sodium ion battery
CN116364854A
Cited By
Lithium ion battery negative pole piece and preparation method thereof
CN120545306A